Low-dose decitabine priming endows CAR T cells with enhanced and persistent antitumour potential via epigenetic reprogramming - Wang, Yao; Tong, Chuan; Dai, Hanren; Wu, Zhiqiang; Han, Xiao; Guo, Yelei; Chen, Deyun; Wei, Jianshu; Ti, Dongdong; Liu, Zongzhi; Mei, Qian; Li, Xiang; et al. (Nature communications, 2021)
Insufficient eradication capacity and dysfunction are common occurrences in T cells that characterize cancer immunotherapy failure. De novo DNA methylation promotes T cell exhaustion, whereas methylation inhibition enhances T cell rejuvenation in vivo. Decitabine, a DNA methyltransferase inhibitor approved for clinical use, may provide a means of modifying exhaustion-associated DNA methylation programmes. Herein, anti-tumour activities, cytokine production, and proliferation are enhanced in decitabine-treated chimeric antigen receptor T (dCAR T) cells both in vitro and in vivo. Additionally, dCAR T cells can eradicate bulky tumours at a low-dose and establish effective recall responses upon tumour rechallenge. Antigen-expressing tumour cells trigger higher expression levels of memory-, proliferation- and cytokine production-associated genes in dCAR T cells. Tumour-infiltrating dCAR T cells retain a relatively high expression of memory-related genes and low expression of exhaustion-related genes in vivo. In vitro administration of decitabine may represent an option for the generation of CAR T cells with improved anti-tumour properties. De novo DNA methylation has been associated with T cell exhaustion in cancer immunotherapy. Here the authors show that the pre-treatment of CD19 CAR-T cells with the DNA methyltransferase inhibitor decitabine limits exhaustion and confers enhanced proliferative, effector and memory properties upon antigen exposure, with improved tumor control.